THE CULTIC AND HYMNOGRAPHIC FIGURE OF SAINT SIMEON IN THE CONTEXT OF TRANSLATED SLAVIC LITERATURE (Philological Studies, 2025)
Focusing on the conceptual elements of the first Serbian national cult that are general and shared with culturally related civilizations, this paper aims to examine the contribution of the common heritage to its genesis, offering an overview of the most significant connections and outlining a direction for their future interpretation. The first section will be dedicated to general considerations regarding the relationship between 13th-century Serbian hymnography and translated, particularly biblical, literature. The following part will explore the connections between the cult of Saint Simeon and the cults of saints who are ideologically and thematically close to him. The central chapter will discuss the relationship between Saint Simeon and Saint Demetrius of Thessaloniki within the broader context of the Slavic reception of the cult of this Byzantine saint. The concluding section of the paper will offer a comparative analysis of Saint Sava’s Service to Saint Simeon in light of the Service to Saint Simeon Stylites, drawing on earlier scholarship. The goal of the study is to shed light on the cult of Saint Simeon within a broader cultural framework beyond the Serbian context, which is especially important in affirming the participation of Serbian culture and literature in the shared spiritual life of the Orthodox oikoumene – thereby suggesting that the value of its original contributions is indeed universal.